Outcomes and Quality of Life in Patients with Upper Limbs Amputations in Cotonou National Teaching Hospital- Benin - Tidjani, Iréti Fiacre; Lawson, Eric; Ouangre, Abdourahmane; Chigblo, Pascal; Alagnide, Etienne; Boko, Marius; Madougou, Soumaïla; Akue, Aristote Hans-Moevi (European Scientific Journal, ESJ, 2019)
Background: Upper limbs amputations disturb relational life. Outcomes of upper limb amputees were studied, functional outcomes and quality of life were analyzed. Objectives: The purpose of this study was to examinate the outcomes of an upper limb amputation on a functional, social and economic level, and to investigate the epidemiological and clinical factors that bear the functional outcomes and quality of life of these patients. Methods: an analytical prospective study over seven years which included 37 patients managed at the referral hospital in Benin was performed. They were mean aged of 36.3 years and 22 were in couple. The mean time of follow-up was 3.0 ± 2.1 years. The rate of fitting prosthesis, relateralization, presence of bi-manual activity, Disabilities of the Arm, Shoulder and Hand (DASH) score, handicap imposed by the amputation, and its socio-economic impact were recorded. Quality of life of amputees evaluated using Nottingham Health Profile (NHP) score was also studied. Statistical analysis was performed with Chi2 and Kruskal-Wallis tests. A p-value ≤0.05 was established as statistically significant. Results: No patient had been fitted; one had been able to re- lateralize; 24 patients demonstrated bi-manual activity. The mean DASH score was 40.1 ± 13.7. Thirteen patients were able to dressthemselves and 10 needed an additional help to go to the toilet. Socially, 21 patients had given up their hobbies, and 5/22 were no longer in a couple. Economically, 27 patients had a decreased monthly income. Factors influencing functional outcomes were the level of amputation and gender (p of 0.005 and 0.006, respectively). The mean NHP score was 5.8 ± 0.2. There was a statistically significant relationship between quality of life, age and level of amputation (p of 0.02 and 6x10-4, respectively). Conclusion: Upper limb amputations strongly affect quality of life. A better social reintegration policy for upper limb amputees should be contemplated in Benin.